NOVICE ENGLISH TEACHER’S PROBLEMS AND STRATEGIES IN IMPROVING YOUNG LEARNERS’ MOTIVATION DURING ONLINE LEARNING - Santoso, Nur Amanah; Purnawarman, Pupung; Sudana, Dadang (Universitas Muhammadiyah Makassar, 2025)
Studies reveal concern about students’ decreased motivation in the pandemic online learning, and novice teachers are especially vulnerable in this era as they still have little teaching experiences but have to teach in such a challenging environment. This paper investigates the problems a novice teacher faced in improving elementary students’ motivation during online learning and the motivational strategies she used. The data were collected through a semi-structured interview and presented according to the narrative inquiry design. The results imply that the novice teacher had troubles related to the lack of access to a real-time, face-to-face communication platform that allows direct feedback, students’ low motivation in submitting their tasks, and her lack of teaching experience. The novice teacher had used some motivational strategies which include relating the learning topic with the student's interest and context, utilizing various learning media and material, increasing the students’ expectancy of success, and encouraging positive self-evaluation. The novice teacher had implemented the motivational strategies to some extent and handled the problems quite well; however, there is still a lack of variety in her motivational strategies and a lack of teaching experience. Therefore, the teacher should continuously self-reflect and improve her knowledge and practice, institutions must ensure that novice teachers are not left to adapt on their own, and policies must prioritize equitable access to learning technologies and family engagement strategies to support children’s learning at home.